Phylogeny and Pathology of Anisakids Parasitizing Stranded California Sea Lions (Zalophus californianus) in Southern California - Hrabar, Jerko; Smodlaka, Hrvoje; Rasouli-Dogaheh, Somayeh; Petrić, Mirela; Trumbić, Željka; Palmer, Lauren; Sakamaki, Kristen; Pavelin, Tina; Mladineo, Ivona (Frontiers in Marine Science, 2021)
In marine mammals, nematode-inflicted pathological lesions combined with other pathogens and factors (i.e. pollution, climate change, domoic acid poisoning events, seasonal El Nino starvation events), negatively impact pinnipeds’ health and may cause mortality. Five California sea lions (Zalophus californianus); a female pup, three male yearlings and an adult female, suffered mortalities during rehabilitation at the Marine Mammal Care Center Los Angeles (San Pedro, CA). According to the necropsy reports, animals developed multisystemic parasitism as a leading cause of death, combined with malnutrition and hypoglycemia. In order to reveal host-parasite dynamics that may play a role in pinniped health and recovery, we examined the type and level of histopathological stomach lesions in California sea lions caused by anisakid nematodes. All isolated anisakids were morphologically and molecularly identified, and their phylogenetic relationships were reconstructed using the sequence of the mitochondrial COII gene. The lesions were presented as chronic granulomatous gastritis, with moderate edema and hyperemia of the tunica submucosa and lamina propria, followed by mild, focal fibrosis of the gastric wall. Ulcerative changes with mixed leukocytic infiltrate showed to be localized, shallow, non-perforative and with no apparent bacterial coinfection, mostly accompanied by healing granulation tissue. Isolated anisakids grouped in three distinctively separated monophyletic clades corresponding to genera Anisakis, Contraceacum and Pseudoterranova. Most abundant were representatives of C. ogmorhini sensu lato (55.36%), followed by A. pegreffii (23.21%), P. azarasi (17.86%), P. decipiens sensu lato (1.79%) and A. simplex (1.79%). Phylogenetic trees revealed no differentiation at intra-species level. Our analysis of divergence revealed Contraceacum separated from other lineages in the Jurassic period at the 176.2 Mya and Anisakis diverging from Pseudoterranova in Cenozoic period at 85.9 Mya.